Systematic Literature Review: Commognitive dan Kemampuan Komunikasi Matematis - Usman, Muhammad Rizal; Husniati, Andi; Kristiawati, Kristiawati (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to analyze the relationship between commognitive theory and students’ mathematical communication skills at the secondary education level, specifically in junior and senior high schools. This review is motivated by the importance of understanding students' thinking processes in expressing mathematical ideas verbally, visually, symbolically, and procedurally. Commognitive theory, which comprises four main components word use, visual mediators, narratives, and routines provides a conceptual framework for examining the dynamics of students’ mathematical discourse. The method employed is a Systematic Literature Review (SLR) following the PRISMA protocol. A total of 26 articles were analyzed, sourced from the Scopus and Google Scholar databases, with inclusion criteria covering publications from 2013 to 2024 relevant to the topic and the context of secondary school students. The findings were categorized into three major themes: (1) the application of commognitive theory in mathematics instruction at the secondary level; (2) indicators of students’ mathematical communication in written, oral, and visual forms; and (3) the interrelation between commognitive components and dimensions of mathematical communication. The review reveals that students exhibit varying tendencies in activating commognitive components depending on the type of task and the mode of problem presentation. Nevertheless, the explicit integration of commognitive theory and mathematical communication indicators has not yet been thoroughly explored. The implications of this review highlight the urgency of developing discourse-based assessment instruments, as well as designing challenging tasks that foster student engagement across all aspects of mathematical thinking and communication.